2016
DOI: 10.1007/s10555-016-9633-1
|View full text |Cite
|
Sign up to set email alerts
|

Telomeres and telomerase in head and neck squamous cell carcinoma: from pathogenesis to clinical implications

Abstract: Strongly associated with tobacco use, heavy alcohol consumption, and with high-risk human papillomavirus (HPV) infection, head and neck squamous cell carcinoma (HNSCC) is a frequently lethal, heterogeneous disease whose pathogenesis is a multistep and multifactorial process involving genetic and epigenetic events. The majority of HNSCC patients present with locoregional advanced stage disease and are treated with combined modality strategies that can markedly impair quality of life and elicit unpredictable res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 193 publications
2
36
0
Order By: Relevance
“…Recently, the targeting of telomeres gained much attention for its therapeutic anticancer effects [14][15][16]. In this study, we confirmed that silencing the genes related to telomerase and ALT mechanisms is associated with inhibiting tumor growth in vivo, consistent with our previously published results [9].…”
Section: Discussionsupporting
confidence: 92%
“…Recently, the targeting of telomeres gained much attention for its therapeutic anticancer effects [14][15][16]. In this study, we confirmed that silencing the genes related to telomerase and ALT mechanisms is associated with inhibiting tumor growth in vivo, consistent with our previously published results [9].…”
Section: Discussionsupporting
confidence: 92%
“…18,19 Different studies observed that patients with short telomeres have a higher risk of developing HNC. [9][10][11][12]18,20 Short LTL associated with an increased risk of developing oral premalignant lesions (OPL) and oral squamous cell carcinoma (OSCC), suggesting that patients with OPL and short LTL have an increased risk to progress to OSCC. Indeed, patients who have OSCC and short LTL have the worst prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, the association between telomere length (TL) and the risk of developing cancers is still conflicting among studies. [9][10][11][12] The head and neck cancer (HNC) represents the sixth most common cancer worldwide. 5 Non-small cell lung tumors present shorter telomeres compared with telomeres in control tissues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Checkpoint-compromised cells can escape cellular senescence and apoptosis and potentially reactivate telomerase expression to drive telomere maintenance and replicative immortality. 67 There is growing interest in studying the interplay of telomere/ telomerase as a key determinant for genomic stability, with most studies indicating that they are detectable at the premalignant stage of various cancer types. 68 However, there are no studies assessing the telomeres in PPOELs.…”
Section: Immortalizationmentioning
confidence: 99%